Transformational Leadership of School Administrators under Sakaeo Primary Educational Service Area Office 1 - แถลงเรียบ ยุวดี; ชวศิริกุลฑล นันทนา; รักษนคร กุลจิรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research were 1) to study the transformational leadership of school administrators 2) to compare the transformational leadership of school administrators; and 3) to explore guidelines for developing the transformational leadership of school administrators, categorized by gender, age, educational level, and school size. The sample included 319 teachers from the Sa Kaeo Primary Educational Service Area Office 1 (2025 academic year), selected via Taro Yamane’s formula followed by stratified and simple random sampling. Additionally, five key informants—three department heads and two teachers—were interviewed. Research instruments comprised a semi-structured interview form and a 5-point Likert scale questionnaire (reliability = .99). Data analysis involved frequency, percentage, mean, standard deviation, t-test, F-test, Scheffé’s post-hoc test, One-way ANOVA, and content analysis. The research findings were as follows: 1) The transformational leadership of school administrators, both overall and each aspect, were at a high level. 2) Comparisons by gender, educational level, and school size showed no significant differences. However, work experience showed significant differences at the .01 level. Scheffé’s test indicated that teachers with 5-10 years of experience reported higher mean scores in idealized influence than those with less than 5 years and more than 15 years of experience, while differences in inspirational motivation, intellectual stimulation, and individualized consideration were found between teachers with 5-10 years and more than 15 years of experience at the .05 level. 3) Development guidelines suggest that school administrators should strengthen all dimensions of transformational leadership: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration to enhance educational quality.